Concepts and Contexts: The Interplay of Philosophy and History in Understanding Human Society - Rashid Manzoor Bhat; Silllalee A/L S. Kandasamy; P. Rajan (Formosa Journal of Applied Sciences, 2023)
This study aims to investigate the historical development of philosophical thought and its impact on the interpretation of historical events and processes, identify the main philosophical concepts that have influenced historical methodology, and explore the ways in which historical events and societal changes have shaped philosophical thinking and thinking. lecture. Employing a combination of descriptive, analytical, and historical research methods, this study used a comprehensive literature review, content analysis, examination of case studies, and interviews with philosophers and historians to address these objectives. The significance of this research lies in its potential to enhance understanding of the interdependence between philosophy and history, ultimately cultivating a more nuanced perspective of human society.